An Expert System For Diagnosing Tonsylliti Disease Using Web-Based Forward Chaining Method - Feri Ramadiansyah; Herlina Latipa Sari; Prahasti Prahasti (Penerbit Jurnal Indonesia, 2022)
Tonsillitis is inflammation of the palatine tonsils, which are part of the Waldeyer ring. Spread of infection through air borne droplets, hands and kissing. 4,5 Tonsillitis is more common in children aged 5-15 years with a prevalence of bacterial tonsillitis 15-30% in children with throat disorders and 5-15% in adults with throat disorders. The author received data that in the past year there were 63 patients suffering from tonsillitis, both acute and chronic. It can be concluded that every month there are 5-6 people from various regions in Bengkulu Province who suffer from tonsillitis and receive treatment at the Rafflesia Hospital. But the problem in the medical world is an imbalance between patients and doctors. In addition, most people are not medically trained, therefore the author intends to design an